DOMESTIC VIOLENCE IN THE WAKE OF COVID-19: INTERVENTION MEASURES TO AMELIORATE THE IMPACT (UUM Journal of Legal Studies, 2023)
Reports of domestic violence cases saw a huge uproar during the Coronavirus pandemic in 2019. The height of domestic violencefollowing the pandemic has had a critical impact universally. There is a pressing call for responding to these acts of domestic violence,and this article investigates conceivable measures and practices to moderate the impact of domestic violence and help these victims out of their abusive environment, especially during pressing times like the COVID-19 eruption. This study takes on a doctrinal examination of existing materials, including an evaluation of the Domestic Violence Act 1994, articles, diaries, and other forms of writing in relation to the current concerns. The discoveries have exhibited that the existing framework comes up short on the foundation of helping and directing the targets out of their abusers at home in conditions of undertakings like the pandemic. Multiple forms of undertakings are expected to introduce better coordination among every vital section of society, including health, education, police, the court, and community groups, in order to embed adequate preventive measures to mitigate the consequences.